2022
DOI: 10.1002/brb3.2569
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of poststroke cognitive impairment by intermittent theta bursts: A double‐blind randomized controlled trial

Abstract: Background: Intermittent theta burst stimulation (iTBS) is known to improve cognitive impairment caused by Alzheimer's disease and Parkinson's disease, but studies are lacking with respect to the efficacy of iTBS on poststroke cognitive impairment (PSCI).Objective: This study was conducted to investigate the effect of left dorsolateral prefrontal cortex (DLPFC) iTBS on improving cognitive function in stroke patients.Methods: Fifty-eight patients with PSCI are randomly divided into iTBS (n = 28) and sham stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 50 publications
0
43
0
2
Order By: Relevance
“…A total of 814 studies were obtained, including 353 in English and 461 in Chinese. 18 studies (Kim et al, 2010 ; Lu et al, 2015 ; Yun et al, 2015 ; Shaker et al, 2018 ; Yin et al, 2018 ; Zeng et al, 2019 ; Zhang and Zou, 2019 ; Liu et al, 2020 , 2021 ; Li Y. et al, 2020 ; Ma et al, 2020 ; Ai et al, 2021 ; Li H. et al, 2021 ; Zhang et al, 2021 ; Chen et al, 2022 ; Ko et al, 2022 ; Li W. et al, 2022 ; Yan et al, 2022 ) were finally included, including 9 in English (Kim et al, 2010 ; Lu et al, 2015 ; Yun et al, 2015 ; Shaker et al, 2018 ; Liu et al, 2020 ; Li Y. et al, 2020 ; Li H. et al, 2021 ; Ko et al, 2022 ; Li W. et al, 2022 ) and 9 in Chinese (Yin et al, 2018 ; Zeng et al, 2019 ; Zhang and Zou, 2019 ; Ma et al, 2020 ; Ai et al, 2021 ; Liu et al, 2021 ; Zhang et al, 2021 ; Chen et al, 2022 ; Yan et al, 2022 ). The literature selection process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 814 studies were obtained, including 353 in English and 461 in Chinese. 18 studies (Kim et al, 2010 ; Lu et al, 2015 ; Yun et al, 2015 ; Shaker et al, 2018 ; Yin et al, 2018 ; Zeng et al, 2019 ; Zhang and Zou, 2019 ; Liu et al, 2020 , 2021 ; Li Y. et al, 2020 ; Ma et al, 2020 ; Ai et al, 2021 ; Li H. et al, 2021 ; Zhang et al, 2021 ; Chen et al, 2022 ; Ko et al, 2022 ; Li W. et al, 2022 ; Yan et al, 2022 ) were finally included, including 9 in English (Kim et al, 2010 ; Lu et al, 2015 ; Yun et al, 2015 ; Shaker et al, 2018 ; Liu et al, 2020 ; Li Y. et al, 2020 ; Li H. et al, 2021 ; Ko et al, 2022 ; Li W. et al, 2022 ) and 9 in Chinese (Yin et al, 2018 ; Zeng et al, 2019 ; Zhang and Zou, 2019 ; Ma et al, 2020 ; Ai et al, 2021 ; Liu et al, 2021 ; Zhang et al, 2021 ; Chen et al, 2022 ; Yan et al, 2022 ). The literature selection process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…All studies were blinded to treatment participants. Ten studies (Kim et al, 2010 ; Yun et al, 2015 ; Yin et al, 2018 ; Zhang and Zou, 2019 ; Liu et al, 2020 , 2021 ; Li Y. et al, 2020 ; Ai et al, 2021 ; Ko et al, 2022 ; Li W. et al, 2022 ) were blinded to assessors. The results of all studies were complete and not selectively reported.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations